In Search of Lost Time - Proust, Marcel; Moncrieff, C. K. Scott, tr.; Kilmartin, Trence, tr. (Britain Vintage, 2002)
Contents: v.1. Swann's Way (xii, 522 p.),- v.2. Within A Budding Grove (634 p),- v.5. The Captive The Fugitive (814 p.).
Library has vol 1, vol 2 and vol 5 only